Afghanistan: Deja vu or a new beginning - Sinha, Amar. (U.S.I Journal)
The long-negotiated agreement to bring peace to Afghanistan appears to be floundering. While the political standoff between the two leading contenders to Presidency has since defused, and a modus vivendi based on power sharing arrived at, commencement of the much awaited intra- Afghan negotiations are delayed. A successful outcome of Afghan reconciliation will bring to naught decades of support to Taliban from some quarters, which successfully chipped away the international resolve to oppose all terrorist activities in, and emanating from, Afghanistan. But this does not suit some parties. This creates a delicate situation that can easily slip out of control due to continuing gruesome violence even when claimed by other extremist groups operating under new flags and symbols. India has been steadfast in its support to the government of the Islamic Republic of Afghanistan. Despite the adverse security situation, India has continued with its developmental projects. India$1 (Bs future policy needs to be based on certain realities which the article brings out. - Reproduced s